Madrasah based management through the implementation of ISO 21001:2018: A case study at Madrasah Istiqlal Jakarta - Mufassirul Alam; Aas Siti Sholichah; Sarwenda Sarwenda; M. Taufiqurrahman; Ahmad Solihin (Kuras Institute, 2026)
Purpose – The purpose of this study is to examine the implementation of Madrasah-Based Management through the adoption of the ISO 21001:2018 Educational Organizations Management System at Madrasah Istiqlal Jakarta and to evaluate its contribution to strengthening institutional governance and improving the quality of educational services. Method – This study employed a qualitative case study design. Data was collected through observations, semi-structured interviews, document analysis, and an examination of institutional policies related to the implementation of ISO 21001:2018. Data was analyzed using the interactive model of data reduction, data display, and conclusion drawing. Findings – The findings indicate that the implementation of Madrasah-Based Management through ISO 21001:2018 strengthened organizational governance, enhanced the effectiveness of educational services, improved human resource professionalism, and fostered a sustainable quality culture. Specifically, the study found that (1) standardized operating procedures were implemented across all academic and administrative units, improving consistency, transparency, and institutional accountability; (2) Key Performance Indicators (KPIs), periodic internal quality audits, and evidence-based decision-making were systematically integrated into performance evaluation and continuous quality improvement; and (3) stakeholder participation—including teachers, administrative staff, parents, and the madrasah committee—increased substantially through structured planning, evaluation, and institutional decision-making processes. These empirical findings demonstrate that ISO 21001:2018 has enabled Madrasah Istiqlal Jakarta to establish a structured, accountable, learner-centered, and adaptive management system while preserving its Islamic educational values